System of Environmental-Economic Accounting 2012 : Central Framework. (Manuals and Guides, 2017)
Comparable and reliable data supporting coherent analytical and policy frameworks are essential elements to inform debates and guide policy related to the interrelationships between the economy and the environment. "The System of Environmental-Economic Accounting 2012-Central Framework" (SEEA Central Framework) is a statistical framework consisting of a comprehensive set of tables and accounts, which guides the compilation of consistent and comparable statistics and indicators for policymaking, analysis and research. It has been produced and is released under the auspices of the United Nations, the European Commission, the Food and Agriculture Organization of the United Nations, the Organisation for Economic Co-operation and Development, the International Monetary Fund, and the World Bank Group. The SEEA-Central Framework reflects the evolving needs of its users, new developments in environmental economic accounting and advances in methodological research.